Injuries resulting from practicing performance sports in table tennis and tennis - Review - Mircea-Dan, M.; Mereuta, C.; Iordan, D.-A. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2020)
Performance sport as an area of human excellence requires, besides an over-average genetic endowment of motor skills, a huge workload of high intensity, which causes the wear of the body systems of the athletes, especially the osteo-musculo-articular. The high ball movement speed for rocket and paddle sports disciplines such as table tennis and field tennis, intensively demands the performance of the body of practitioners when performing specific technical tactics, especially the technical elements of the attack, such as topspin or smash. Based on the theoretical documentation, I noticed an acute condition in the scapulo-humeral joint 21.05%, at the lumbar level 15.79% and 13.16% in the ankle joint in the table tennis and in the field tennis as percentages at scapulo-humeral joint 13.85%, lumbar 15.38% and 20.00% ankle joint, aspects that validate our desire to improve the quality of life of practicing athletes of the two disciplines through a program of amelioration of compensatory nature. The objective of this theoretical research is to identify the areas subject to mechanical stress with high risk of wear or injury from the two "sister" sports disciplines. Tasks: Critical analysis of a larger volume of studies conducted on the direction of our research interest. Purpose: obtaining the information necessary which would highlight the risks the performance athletes, practitioners of the two disciplines, are subjected to, as well as gaining knowledge on tennis and table tennis.